Unseen: a 3D immersive experience game for visually impaired individuals - Rodrigues, Claudia Susie C.; Nazareth, Vitoria; Azevedo, Ramon O.; Barbosa, Priscyla; Werner, Cláudia (Anais do Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de Jogos (WIPlay); 2023: Anais do II Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de Jogos, 2023)
The increasing importance of accessibility, particularly in disability rights, is evident. "Unseen" is a prototype with binaural audio technology to create an immersive 3D gaming experience to promote accessibility and digital inclusion. It aims to provide an immersive audiogaming experience for both sighted gamers and visually impaired people. An evaluation of the prototype was conducted to verify users’ understanding of audiogame interactions and to determine the effectiveness of the developed mechanisms. Valuable information was collected through laboratory tests that helped identify areas for the game improvement as well as the elements that left users satisfied and motivated. These research results notably exemplify promoting digital accessibility in gaming and engaging individuals with visual impairments in the virtual world.